Compositional changes of major chemical compounds in Greek carob pods during development - A.S. Vekiari; G. Ouzounidou; G. Gork; M. Ozturk; M. Asfi (Bulletin of the Chemical Society of Ethiopia, 2012)
Because of the strong association with health benefits of some chemical compounds contained in carob fruit the composition of chemical substances of two common type carob pods (Ceratonia siliqua L.) and their changes during fruit developing in two periods of harvesting were reported. Samples were originated from a site near Rethymno, Crete Island, at an altitude of 100 m above the sea level. The moisture content determined through sample’s drying in 70 oC under vacuum, sugars by HPLC (high pressure liquid chromatography), total polyphenols by ultraviolet/visible (UV/Vis) and fatty acids by gas chromatography (GC) in the fleshy and wild types were determined at three stages of development. Principal sugars found were glucose, fructose and sucrose. The predominant fatty acid was linoleic acid (n-6) followed by oleic, palmitic and then linolenic (n-3) fatty acids. The total unsaturated fatty acids content was two times higher than the content of total saturated fatty acids in fully-developed carob pod. The ratio n-6/n-3 was under 5, showing a good equilibrium between the two essential fatty acids. The fully developed fruits of both varieties revealed lower contents of polyphenols, proteins and sugars compared with their previous growth stages. The fleshy carob pods exceed the wild variety in concentration of proteins, sugars and fatty acids, while the wild variety exceeds the fleshy in polyphenols concentration.DOI: http://dx.doi.org/10.4314/bcse.v26i3.3